Expression and Clinical Significance of miR-146a and Tumor Necrosis Factor Receptor-Associated Factor 6 (TRAF6) in Myasthenia Gravis Patient Serum. (21st April 2021) - Yan, Mei; Fu, Yue; Rao, Hui; Zhou, Huiling; Liang, Xiaohuang
Abstract : Objective . To investigate the expression and clinical significance of miR-146a and tumor necrosis factor receptor-associated factor 6 (TRAF6) in myasthenia gravis (MG) patient serum. Methods . The serum of 52 patients with MG and 60 healthy individuals was collected in our hospital. The expression of miR-146a and TRAF6 in serum was measured by real-time PCR (RT-PCR). Comparison among serum miR-146a and TRAF6 mRNA group clinical characteristics and assorted expressions was done with the correlation among the two groups evaluated. Logistics regression was used to analyze the effect of miR-146a and TRAF6 mRNA on MG development with the ROC curve applied for an investigation into the diagnostic role of miR-146a and TRAF6 mRNA expression in MG development. Results . miR-146a and TRAF6 mRNA were significantly increased in the patients with MG compared with the healthy controls. Significant differences were identified in respiratory muscle endurance, muscle weakness level, vital capacity, and maximal voluntary ventilation between the two groups. Additionally, correlation analysis has discovered a positive correlation between miR-146a and TRAF mRNA expression in patients with MG. miR-146a and TRAF6 mRNA are independent MG occurrence factors exhibited by multivariate analysis while areas under ROC curve (AUCs) of miR-146a and TRAF6 mRNA in MG diagnosis were established by ROC curve analysis with results being 0.782 and 0.703, correspondingly. Conclusion . miR-146a and TRAF6 mRNA are highly expressed in MG patients and can affect MG occurrence. miR-146a is a suitable candidate marker for diagnosing MG.